2015
DOI: 10.1007/s00394-015-0982-2
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid supply with complementary foods and LC-PUFA status in healthy infants: results of a randomised controlled trial

Abstract: www.clinicaltrials.gov , identifier: NCT01487889, title: Polyunsaturated fatty acids in child nutrition-a German multimodal optimisation study (PINGU).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…The RBC-DHA and RBC-AA observed in children were comparable to those in a randomized controlled trial of healthy German infants, where complementary foods either enriched with ALA-rich rapeseed oil, LA-rich corn oil or salmon (DHA), were given from the age of 4 months until age of 10 months [30]. In that trial, the RBC-DHA in the two groups with rapeseed oil and corn oil declined from 5.9% to 4.5%, that was even lower than observed in our study (4.9%).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The RBC-DHA and RBC-AA observed in children were comparable to those in a randomized controlled trial of healthy German infants, where complementary foods either enriched with ALA-rich rapeseed oil, LA-rich corn oil or salmon (DHA), were given from the age of 4 months until age of 10 months [30]. In that trial, the RBC-DHA in the two groups with rapeseed oil and corn oil declined from 5.9% to 4.5%, that was even lower than observed in our study (4.9%).…”
Section: Discussionsupporting
confidence: 66%
“…One explanation for the higher level of DHA in the Nepali women may be that they had a considerably lower fat intake, about one third of the Chilean women. ALA and LA are essential fatty acids and can to some extent be desaturated and elongated to DHA and AA, respectively [30] and low-fat diets have been associated with significantly higher levels of DHA in intervention trials [55,56]. In addition, the Chilean women had a relatively high intake of LA 4.4 g/day (median), which can adversely affect the EPA and DHA formation [47].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that breastfeeding, Fatty acid dehydrogenase (FADS) genotype and fish intake are important determinants of blood DHA status in late infancy, with each 10-g increment in fish intake being associated with a 0.3 FA% increase in DHA status [87]. Four studies have investigated the effect of supplying additional LCPUFA or precursor fatty acids in CF, demonstrating effects on red cell or plasma fatty acid status [88][89][90][91], although only one study incorporated a clinical outcome; breast-fed infants randomised to receive jar per day of weaning foods containing DHA-enriched egg yolk had a greater increase in visual acuity resolution by months than those fed control baby food. Two additional trials investigated the role of LCPUFA supplementation of infant formulae during the CF period, with infants randomized to LCPUFA-supplemented versus unsupplemented formulae when they stopped breast-feeding at either 6 weeks [92] of age or 4 to 6 months [93] of age.…”
Section: Lcpufa Intakementioning
confidence: 99%
“…Their observation, if confirmed in larger studies, suggests that breastfed and formula-fed infants alike may need increased monitoring for iron deficiency, because concerns about giving excessive iron may lead to lower levels of iron fortification in formula and infant foods. 3 Iron deficiency may well become more common in Europe and the US even as evidence mounts indicating poorer developmental and behavioral outcomes with iron deficiency with or without anemia. [4][5][6] Current hemoglobin screening detects anemia but not iron deficiency, however, and thus, protecting the developing child from too little or too much iron remains challenging.…”
Section: Replymentioning
confidence: 99%